A Richards growth model to predict fruit weight. (5th January 2023) - Gerhard, Daniel; Moltchanova, Elena
Summary: The Richards model comprises several popular sigmoidal and monomolecular growth curves. We illustrate fitting of a Bayesian Richards model by splitting the full growth model into several submodels, followed by a model selection procedure. The performance of the methodology is evaluated by Monte Carlo simulations. A double‐sigmoidal version of the Richards model is applied to model grape bunch weight based on data from a New Zealand vineyard over a single growing period. A Bayesian Richards growth model applied to grape size data. Representations of phenological processes are selected through multi‐model inference.